Neuroplasticity and its implications for rehabilitation - López Roa, Lina María (Universidad y Salud, 2012)
Brain plasticity is a term widely used in recent years, but its study originates from the beginnings of neurology. This brain power to use functional adaptation mechanisms that minimize the damage after an injury, as well as the ability to acquire new knowledge even in very old age, make brain malleability a unique and useful in rehabilitation. This leads to the realization of a review of the theme that allows knowing the history, the mechanisms of empowerment as well as the utility in neural rehabilitation processes.